Pendampingan Kegiatan Seminar Hasil Penelitian Tindakan Kelas Pada Guru-Guru SDI Mbongawani - Nining Sar'iyyah; Vivien Restianim; Manggu Ngguna Raji; Yuliani Sepe Wangge; Gregorius Sebo Bito (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
This activity aims to increase the understanding of SDI Mbongawani Ende teachers regarding the implementation of the seminar on the results of classroom action research. This activity also aims to help the teachers collect documents on the implementation of the seminar so that it can be used as evidence attached to the proposed promotion file. This activity was attended by teachers and principals of SDI Mbongawani, lecturers, group heads and teachers from related clusters. This activity was carried out in two stages, namely the preparation stage and the seminar implementation stage. At each stage, teachers are guided and trained to prepare, implement and document evidence of classroom action research seminars. The results of this activity have an impact on increasing the understanding of SDI Mbongawani teachers regarding the implementation of the seminar on the results of classroom action research.